17β‐Estradiol Protects Human Eyelid‐Derived Adipose Stem Cells against Cytotoxicity and Increases Transplanted Cell Survival in Spinal Cord injury. Issue 2 (22nd December 2013) - Zhou, Jing; Lu, Ping; Ren, Hao; Zheng, Zefeng; Ji, Junfeng; Liu, Hua; Jiang, Fangzhen; Ling, Shucai; Heng, Boon Chin; Hu, Xueqing; Ouyang, HongWei
Abstract Stem cell transplantation represents a promising strategy for the repair of spinal cord injury (SCI). However, the low survival rate of the grafted cells is a major obstacle hindering clinical success because of ongoing secondary injury processes, which includes excitotoxicity, inflammation and oxidative stress. Previous studies have shown that 17b‐estradiol (E2) protects several cell types against cytotoxicity. Thus, we examined the effects of E2 on the viability of human eyelid adipose‐derived stem cells (hEASCs) in vitro with hydrogen peroxide (H2O2)‐induced cell model and in vivo within a rat SCI model. Our results showed that E2 protected hEASCs against H2O2‐induced cell death in vitro, and enhanced the survival of grafted hEASCs in vivo by reducing apoptosis. Additionally, E2 also enhanced the secretion of growth factors by hEASCs, thereby making the local microenvironment more conducive for tissue regeneration. Overall, E2 administration enhanced the therapeutic efficacy of hEASCs transplantation and facilitated motor function recovery after SCI. Hence, E2 administration may be an intervention of choice for enhancing survival of transplanted hEASCs after SCI.